(untitled) (Biological Sciences - PJSIR, 2015)
Genetically diverse female lines of sunflower were crossed with male testers to get heterotic hybrids. Studies were carried-out during 2008-2010 at Experiment filed of Agriculture Research Institute, Tandojam, Sindh, Pakistan. Six female lines like T-4-0319, PAC-0505, HO-I, Hysun-33, Peshawar-93 and CMS-03 and three testers i.e., PAC-0306, PAC-64-A and SF-187 were crossed in a line ´ tester mating design, thus 18 F1 and F2 hybrids were developed for evaluation of heterosis and inbreeding depression for days to initial flowering, days to maturity, leaves/plant, plant height (cm), head diameter (cm), 1000-achene weight (g), seed yield kg/ha and oil yield kg/ha. The experiment was conducted in a randomised complete block design with four replications. The analysis of variance revealed significant differences among parents, F1s and F2 hybrids for all the traits studied. The existence of significant genetic variability among the plant traits is particularly useful because variations in these traits would allow further improvement in sunflower seed yield and oil traits. The F1 hybrids HO-I ´ PAC-0306 and HO-I PA ´ C-64-A exhibited desirable negative mid and better parent heterosis for days to initial flowering, days to maturity and plant height. These hybrids also manifested desirable positive heterotic effects for leaves/plant, head diameter, 1000-achene?s weight, seed yield and oil yield. Inbreeding depression for phenological, seed yield and oil traits showed that desirable high inbreeding depression was observed in hybrids HO-I ´ P´AC-64-A, HO-I ´ PAC-0306 and HO-I ´ SF-187 for days to initial flowering, similarly T-4-0319 ´ PAC-0306, PAC-0505 ´ SF-187 and HO-I ´ PAC-64-A explicated maximum but rewarding inbreeding depression for days to maturity. The F2 hybrids Hysun-33 ´ SF-187 and Peshawer-93 ´ PAC-64-A may be the most desirable ones in the sense that they recorded comparatively moderate inbreeding depression with enough number of leaves to be productive if F2 hybrids are to be exploited for hybrid vigour. Low inbreeding depression for various traits indicated that such hybrids some how favour the usefulness of F2 hybrids in sunflower.